Tunable 2D Nanomaterials; Their Key Roles and Mechanisms in Water Purification and Monitoring - Fatima, Jawaria; Shah, Adnan Noor; Tahir, Muhammad Bilal; Mehmood, Tariq; Shah, Anis Ali; Tanveer, Mohsin; Nazir, Ruqia; Jan, Basit Latief; Alansi, Saleh (Frontiers in Environmental Science, 2022)
Water supplies around the world are currently heavily polluted by heavy-metal chemicals, synthetic dyes, and other toxic pollutants released by major factories rather than typical household waste. This pollution necessitates adequate monitoring in order to protect natural water sources. There are various wastewater treatment methods available, including nanotechnology i.e., 2D NMs. Rising 2-dimensional nanomaterials including graphene, g-C3N4, MoS2, MXene, black phosphorus, and h-BN have exhibited an unparalleled surface-to-volume ratio, promising ultra-low usage of material, ultrafast handling time, and ultrahigh treatment performance for cleaning and monitoring of water. We provide a current overview of tunable two-dimensional nanomaterials and also on their uses in arising innovations of water such as photocatalysis, isolation, pollutant detection, adsorption, and isolation in this study. The basic architecture techniques of two-dimensional materials are explored, with a focus on their underlying mechanism, physicochemical properties, and intended implementations in various strategies. The study ends with a look at the current problems and various opportunities in two-dimensional material legalized treatment of wastewater and quality monitoring of water. The importance of clean and fresh water to upcoming generations will bring new light and innovations to this emerging sector, allowing it to improve the quality and accessibility of water treatment while also ensuring global water supplies in an increasing part of the world.